Modelling the predation effects of invasive crayfish, Procambarus clarkii (Girard, 1852), on invasive zebra mussel, Dreissena polymorpha (Pallas, 1771), under laboratory conditions. Issue 1 (2nd January 2016) - Gonçalves, V.; Gherardi, F.; Rebelo, R.
Abstract: The functional response of a predator is a key factor regulating the population dynamics of predator-prey systems. This aspect of predatory behaviour must be assessed together with the effects of satiation by overabundant prey when evaluating the potential of biocontrol. The goals of this study were: (1) to identify the consumption rates of juvenile stages of the invasive zebra mussel, Dreissena polymorpha, by the invasive crayfish Procambarus clarkii ; (2) to determine the predator functional response; (3) to evaluate the effects of predator satiation on the intensity of predation; and (4) to model the potential impacts of predation by this crayfish on zebra mussel populations. When presented with a range of mussel abundances, P. clarkii showed a functional response of type II, where the mortality of prey increases with decreasing prey abundance. P. clarkii also exhibited a satiation effect, diminishing its consumption rate from 33 mussels/day to 6 mussels/day over a 6-day period. By combining the effects of the functional response and of predator satiation we produced a model that predicts the complete consumption of local populations of up to 150/160 juveniles by one single crayfish over the period of 1 month. This impact may be important in low-density populations or in populations at equilibrium of D. polymorpha, and will be greater the higher the synchronization between the prey reproductive cycle and the activity period of the predator.